Analysis of Murabahah Financing Marketing Strategy for Gold Installment Products to Increase the Number of Customers at BSI KCP Cemara Asri - Ritonga, Meilinda (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2023)
Introduction: The problem found in this study is that there are still many Indonesians who do not know that they can make gold installments at Islamic banks. people still buy gold through gold shops compared to buying Islamic bank products. it is hoped that this research can help the bank sell its products and help the public to buy gold more easily through Indonesian Islamic banks, especially BSI KCP Cemara Asri. Purpose: The purpose of this study is to find out what strategies are carried out by Bank Syariah Indonesia KCP Cemara Asri in attracting customers to buy their gold installment products. Methodology: The research method used in this study is a descriptive qualitative method using field research methods, which is research using descriptive qualitative methods to explore knowledge about a phenomenon in a certain academic context, with fieldwork carried out at Bank Syariah Indonesia KCP Cemara Asri. Findings: The results obtained from this study are the marketing strategy of gold installment products applied at Bank Syariah Indonesia KCP Cemara Asri using a marketing mix consisting of 7Ps (product, price, place, promotion, people, physical evidence, process).